KREATIVITAS GURU PENDIDIKAN AGAMA KATOLIK DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMA KATOLIK 2 KABANJAHE - Sitepu, Dita Rila; Lumbanbatu, Johannes (Jurnal Bahasa Indonesia Prima (BIP), 2023)
The role of teachers in enhancing students' learning motivation is crucial, especially in catholic religious education. Catholic Religious Education teachers are responsible for being role models, providing inspiration, and motivating students. Teacher creativity is critical n enhancing students' motivation to learn Catholic Religious Education. This research aims to analyze the role of Catholic Religious Education teachers' creativity in motivating students. The research method used is  qualitative with data collection through observation, interviews, and documentation. The research indicate that Catholic Religious Education teachers employ various creative teaching methods and instructional media to enhance students' learning motivation. They implement strategies such as the using pictures, videos, music, group discussions, role-playing, and project assignments. Teachers also assist students in achieving satisfactory learning outcomes by providing guidance, support, and positive feedback. It is expected that the findings of this research will provide a better understanding of the role of Catholic Religious Education teachers' creativity in motivating students and offer valuable  recommendations for teachers and education policymakers.